2017
DOI: 10.3390/plants6040043
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Profile of the Cotton Plant, Gossypium hirsutum: A Review

Abstract: Cotton, Gossypium hirsutum L., is a plant fibre of significant economic importance, with seeds providing an additional source of protein in human and animal nutrition. Flavonoids play a vital role in maintaining plant health and function and much research has investigated the role of flavonoids in plant defence and plant vigour and the influence these have on cotton production. As part of ongoing research into host plant/invertebrate pest interactions, we investigated the flavonoid profile of cotton reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 75 publications
1
48
0
Order By: Relevance
“…Dihydrowyerone acid is a phytoalexin, [37] and 4-Hydroxynonenal is an end product of lipid peroxidation [38]. Stigmasterol was also accumulated in mock inoculated resistant variety, which is an intrinsically existing secondary compound in cotton plant [4]. Elevated levels of fatty acids in resistant cultivar under stress conditions are in accordance with previous findings which suggest their role in signal transduction [39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Dihydrowyerone acid is a phytoalexin, [37] and 4-Hydroxynonenal is an end product of lipid peroxidation [38]. Stigmasterol was also accumulated in mock inoculated resistant variety, which is an intrinsically existing secondary compound in cotton plant [4]. Elevated levels of fatty acids in resistant cultivar under stress conditions are in accordance with previous findings which suggest their role in signal transduction [39].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to fiber, cotton seed offers a supplemental income and it is a source of protein for human and animal nutrition. G. hirsutum is the most commonly grown cotton species and it is native to Mexico and Central America [4]. Cross breeding between diverse upland varieties helped the introduction of upland cotton in different areas of the world [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, differences in light intensity between the two environments likely influenced the relative contributions of NAR and SLA to RGR. Additional differences in environmental conditions such as the influence of wind (Baker et al, 2009), the effect of ultraviolet light (Dehariya et al, 2011), and the need for investment in defense-related metabolites (Olson et al, 2008;Nix et al, 2017) are also known to influence plant growth and could have contributed to the differences observed between the greenhouse and field conditions. In previous studies, similar results were found in that RGR differences were ascribed only to NAR (Eagles, 1967;Pons, 1977), only to LAR (Higgs and James, 1969;Dijkstra, 1989;Smeets and Garretsen, 1986), or to both NAR and LAR together (Jarvis and Jarvis, 1964;Corrẽ, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Loveys et al (2002) studied 16 different plant species including trees, shrubs, grasses, and forbs and reported that under moderate (23°C) or high temperatures (28°C), SLA was the most important factor affecting RGR, whereas at lower temperature (18°C), NAR was the more important determinant of RGR. Additional differences in environmental conditions such as the influence of wind (Baker et al, 2009), the effect of ultraviolet light (Dehariya et al, 2011), and the need for investment in defense-related metabolites (Olson et al, 2008;Nix et al, 2017) are also known to influence plant growth and could have contributed to the differences observed between the greenhouse and field conditions. Additional research would be necessary to ascertain the reasons underlying the environmental effects observed in the present study.…”
Section: Discussionmentioning
confidence: 99%